A Model of Interprofessional Education in the Community with Family Health Approach: Perspectives from Indonesia - Asmara, Fatikhu Yatuni; Kristina, Tri Nur; Afifah, Diana Nur; Bakrie, Saekhol; Dewi, Dian Puspita; Widyandana, Doni; Mawardi, Fitriana; Pamungkasari, Eti Poncorini; Lestari, Endang (Jurnal Keperawatan Soedirman, 2025)
There is no standardized model of interprofessional education (IPE) that is performed in community settings. This study aimed to develop and acquire suggestions for a model of IPE implementation in such environments. This study employed educational design research (EDR) with a qualitative research approach. Step 1 (Analysis and Exploration) was carried out through focus group discussions (FGDs) with students and instructors to explore their experiences with the IPE program, which then proceeds to Step 2 (Design and Construction) by developing a draft model. Eventually, Step 3 (Evaluation and Reflection) was carried out by conducting in-depth interviews with experts to obtain suggestions for the draft model. This study revealed three key themes from FGDs: 1) preparedness of students and families, 2) Coordination, and 3) Students’ assessments. Based on in-depth interviews, the experts provided suggestions categorized into four themes: 1) Characteristics of Participants, 2) Detailed preparation and implementation, 3) Student assessment, and 4) Former thematic definition of health problems. The IPE model in a community setting was perceived as a positive learning experience, and several recommendations were added to increase its effectiveness. Further research is recommended to facilitate broader implementation of the model widely